Pemanfaatan Web Profil sebagai Media Informasi pada UMKM Toko Busana YUKI 2 - Elistya Rimawati; Ari Wibowo; SURYATI GALUH PRAVITASARI; Adi Sanjaya Putra (Redtech Putra Benua, 2025)
The YUKI 2 Clothing Store is a small and medium-sized enterprise (UMKM) specializing in the sale of clothing and household goods, including shirts, pants, shoes, bags, and more. To expand its marketing reach, the YUKI 2 Clothing Store needs to utilize the internet. The purpose of this community service activity is to assist the YUKI 2 Clothing Store in expanding its marketing reach by utilizing Web Information. Data collection methods include observation, interviews, and literature review. The web information contains featured products, new products, the UMKM's address, telephone number, and an admin login page. The creation of this web profile is expected to assist the marketing of the YUKI 2 Clothing Store products in the current digital era. The use of a Web Profile makes the YUKI 2 Clothing Store products more easily recognized by the wider public without the constraints of distance and time, thereby increasing sales